Allied [videorecording (DVD)] - Pitt, Brad, 1963-; Cotillard, Marion, 1975-; Harris, Jared, 1961- (Paramount Home Entertainment, 2017)
The story of intelligence officer Max Vatan, who in 1942 North Africa encounters French Resistance fighter Marianne Beausejour on a deadly mission behind enemy lines. Reunited in London, their relationship is threatened by the extreme pressures of the war.